Cidade para quem? redes de ativismos urbanos na cidade de João Pessoa, PB - Bezerra, Flávia Cristina Coutinho (2022)
This work aimed to analyze the actions and articulations of the urban social movements "Minha Jampa" and "João Pessoa que Quero", which claim participation in the management and strategies of urban planning in the city of João Pessoa (PB). Firstly, for answering the problem proposed in this dissertation — How do these urban social movements understand the city? — it was necessary to analyze some theoretical-methodological references. These references helped us to understand the changes in interpretations of social movements and how was the process of conception of urban activism and their new realities. Indeed, it was observed that community actions revealed several interconnected questions about the right to the city as they sought to exercise some social control of urban public policies, mainly in urban mobility due to the weakness of democratic management from the government in this control. Beyond monitoring the conduct of government practices, urban social movements carried out investigations and critical analyzes on projects and changes in urban and environmental laws that may threaten the rights in and to the city. Then, it was possible to verify that the action of these urban social movements proposed new approaches and tools to encourage broad social participation toward the constitution of a political community that collectively builds the city for all people.